Health‐related quality of life in patients with heart failure eligible for treatment with sacubitril-valsartan - Lena Holmlund; Margareta Brännström; Krister Lindmark; Camilla Sandberg; Karin Hellström Ängerud (Wiley, 2020)
Abstract Aim To describe and compare self‐reported health‐related quality of life between younger and older patients with severe heart failure eligible for treatment with sacubitril-valsartan and to explore the association between health‐related quality of life and age, NYHA classification, systolic blood pressure and NT‐proBNP level. Design Cross‐sectional study. Methods A total of 59 patients, eligible for treatment with sacubitril-valsartan were consecutively included and divided into a younger (≤75 years) and older group (>75 years). Health‐related quality of life was assessed using the Kansas City Cardiomyopathy Questionnaire and the EuroQol 5‐dimensions. Data were collected between June 2016 and January 2018. The STROBE checklist was used. Results There were no differences in overall health‐related quality of life between the age groups. The older patients reported lower scores in two domains measured with the Kansas City Cardiomyopathy Questionnaire, namely self‐efficacy (67.0 SD 22.1 vs. 78.8 SD 19.7) and physical limitation (75.6 SD 19.0 vs. 86.3 SD 14.4). Higher NYHA class was independently associated with lower Kansas City Cardiomyopathy Questionnaire Overall Summary Score.